Desarrollo turístico en comunidades norteamericanas en México: el caso de álamos, sonora - Clausen, Helene Balslev; García, Mario Alberto Velázquez (Diálogos Latinoamericanos, 2010)
The article analyses how a group of North American immigrants in a Mexican city close to the Mexican/US border influences the development of tourism in the region. We propose a new concept intimate experience economy to show how the North American group creates a type of tourism as a form of social activity that permits the tourists to be part of and in contact with scenes, spaces and landscapes far away from their own every day experiences. The article concludes that this way the immigrant group creates the possibility to emphasize certain aspects of the Mexican culture as they believe characterize México.